Faktor Penghalang dan Penggalak Kepatuhan daripada Perspektif Pesakit Tuberkulosis Cicir Rawatan di Kuala Lumpur (Barriers and Motivation Factors towards Treatment Compliance from the Perspective of Defaulted Tuberculosis Patients in Kuala Lumpur) - Mohd Shariff, Noorsuzana; Azhar Shah , Shamsul; Kamaludin, Fadzilah (Penerbit Universiti Kebangsaan Malaysia, 2017)
There is a large volume of published studies describing the adverse relationship between treatment non-adherence with tuberculosis treatment outcome. Non-adherence could result in increased risks of prolonged infectiousness, drug resistance, relapse cases and poor survival among tuberculosis patients. Nevertheless, few studies are to be found providing detailed on the reason of defaulting treatment among tuberculosis patients in Malaysia. Hence the goal of this paper is to find out the barriers and motivations factors that affect patients’ treatment compliance among our local tuberculosis patients. This is a qualitative study which included 12 in-depth interviews with tuberculosis non-compliance patients who were treated at Institute of Respiratory Medicine, Kuala Lumpur. All the conversations were recorded, transcribed and analysed by using thematic analysis. It was found that low knowledge, self-negative attitudes, traditional believes, negative perceptions towards health caregiver, drug side effects, stigma, financial problems, less family support and work commitments are the barriers that prevent the patients from religiously taking their anti-tuberculosis treatment. Meanwhile, factors that encourage them to continue their treatment were the believes of bad effects of the disease onto their lives and health, good relationship between patient and health caregiver and social support from people around them. In conclusion, non-adherence involved a dynamic influence of individual, socio-economic and treatment-related factors on the patients. The results presented here may facilitate improvement in the activities in promoting compliance among tuberculosis patients in the future which tailored to the patients’ specific needs.